Analisis Teologi Sosial Dalam Pemertahanan Identitas Kultural Kesamen Masyarakat Hindu Di Desa Sembiran Buleleng - Miarta Putra, I Nyoman (Jurnal Penelitian Agama Hindu, 2024)
Kesamen, as a local wisdom passed down through generations, is preserved and maintained by the Sembiran community as a core part of their identity. From a social theology perspective, Kesamen represents efforts to uphold ancestral values that emphasize equality and unite the community in a socio-religious framework, while also preventing conflicts of interest. This study aims to examine the Kesamen system in the Sembiran community through the lens of social theology, particularly as a form of cultural identity preservation. The research uses a qualitative approach with data collection methods including observation, interviews, literature studies, and documentation. The findings show that Kesamen values align with the concept of social theology, reflected in daily practices such as Tri Hita Karana, Karma Phala, Tat Twam Asi, and Menyama Braya. Sembiran village is known for its rich traditions and culture, with moral values integrated into various aspects of social life, from individual relationships to community interactions. The preservation of Kesamen holds significant meaning, especially in maintaining religious values, fostering togetherness, ensuring social and cultural sustainability, and stabilizing society. In conclusion, Kesamen plays an essential role in strengthening social cohesion, preserving the cultural identity of the Sembiran community, and resisting external cultural domination. These values also boost the community's confidence in safeguarding their identity and solidarity.